PEMILIHAN DAN BENTUK FUNGSI EMPIRIK DALAM KASUS PENENTU KINERJA PERUSAHAAN - Dyah Sugandini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2008)
This research aims to determine the correct function form in knowing the factorsinfluence the level sale of commodity of retail company middle and top class in YogyakartaSpecial Region Province. The research used the time series secondary data from various theinstitution related to the research. To test the hypothesis concerning the factors influence thesale level, researcher used regression least square analysis. In choosing the function formresearcher applied the MWD test (Mackinon, White, and Davidson) and Error CorrectionModel. The research result show that by paying attention the estimation result of errorcorrection approach, log-linear function form have ability to predicted better relative andconsistent with theory compared to the linear function form.